Strengthening Students' Literacy and Character through Developing Educational Games for Children of Indonesian Migrant Workers in Malaysia - Desi Destiana Agusman; Siti Nur Azizah; Ariel Alvi Zahry; Muhammad Randi Setiadi; Siti Julaeha; Wiwit Saputri; Haliza Putri Maharani; Anika Rahma Putri; Tiana Amalia Putri (Universitas Muhammadiyah Purwokerto, 2024)
Many children of Indonesian Migrant Workers (PMI) are undocumented in Malaysia, causing difficulties in various access areas, one of which is in the education sector. Non-formal education dominates PMI children, influencing children's literacy knowledge, which could be more optimal and impact their weak national character. This study includes empowerment by the Indonesian Young Spirit Foundation (SMI) in the education sector targeting PMI children, which was carried out in Sanggar Belajar (SB) Hulu Kelang and Hulu Langat, Malaysia. The platform for this empowerment is in the form of educational learning activities in the form of word reading and bingo games, which are collaborated with the use of regional songs in gymnastics activities, which are very important to be realized in the context of internalizing literacy knowledge in order to strengthen national character in fulfilling educational rights and strengthening the character of PMI children in Malaysia. It will be carried out from 14 to 21 July 2023. This empowerment uses descriptive qualitative research methods and a Contextual Teaching Learning (CTL) approach in the implementation process. PMI children will receive many benefits from the empowerment carried out by the SMI Foundation, including increased self-confidence in reading aloud, trained verbal skills, positive interactions, an atmosphere of cooperation, improved children's motor skills, and children feel the spirit of cultural values they have learned. The empowerment of this program is hoped to provide sustainable benefits for PMI children and teachers.